Boosting Firm Performance: Insights from the Food & Beverage Sector's Key Drivers - Michael; Widjaja, William (Ilomata International Journal of Tax and Accounting, 2024)
The food and beverage industry is a vital contributor to Indonesia's economy, yet faces challenges in optimizing performance. This study investigates the impact of operating capacity, agency costs, and intellectual capital on firm performance within this sector. Analyzing financial data from 12 out of 26 listed companies spanning 2018 to 2022, with convenience sampling, panel data regression in EViews 12 reveals significant findings. Higher operating capacity positively influences revenue generation, marketing efficacy, and customer satisfaction. Agency costs serve as incentives for managerial alignment with shareholders' interests, enhancing governance and transparency practices. Intellectual capital fosters innovation, operational efficiency, and brand reputation, driving firm performance. The study underscores the strategic importance of these factors in managing firms within the food and beverage industry. For practitioners, insights gleaned from this research offer guidance in formulating effective strategies to enhance operational capacity, manage agency costs, and bolster intellectual capital. Moreover, investors gain valuable insights into assessing investment opportunities in this sector. Policymakers can utilize these findings to formulate policies conducive to fostering growth and sustainability within the food and beverage industry. By addressing these key determinants, firms can bolster their competitive edge and achieve sustained success in the dynamic landscape of the food and beverage sector in Indonesia.